EDUKASI EKONOMI KEUANGAN SYARIAH BAGI SISWA SMAN 1 PADANG DAN SMAN 4 PADANG - Sardiana, Anna; -, Puspita; -, Zulfison; Amalia, Alvien Nur; Darniaty, Will Andilla; Sabila, Salma (LPPM Universitas Islam 45 Bekasi, 2021)
The majority of Indonesian are Muslim. As a country with the largest Muslim population, Indonesia has the potential to develop sharia economics and finance, especially in support of funding the priorities of development, such as infrastructure projects, education, and Agriculture. However, the development of sharia finance in Indonesia is not yet in accordance with expectations. This is reflected by the sharia financial market share including banking and insurance that is still relatively small, which is only reached 8.6 percent until January 2019, specifically for new Sharia banking reached 5.6 percent. Departing from this, it is proposed a community dedication to education regarding the Sharia financial economy. The event was held on 14-15 November 2019. The material presented in relation to values and principles of Sharia economics, and introduction of Sharia banking. Overall the event went smoothly. For the future this activity should be done continuously.